Monitoring the Countermovement Jump Throughout a Netball Season: Potential Implications for Performance - Gibbs, Megan (Auckland University of Technology, 2018)
Netball is a sport which demands high intensity locomotion across the court. As a result, athletes must be physically resilient. While there has been a lot of research on fatigue monitoring and perceived risk of injury, few studies have investigated fatigue in netball and how it influences performance capacity. The aim of this study was to investigate the relationship between acute chronic workload (ACWL) ratios and the capacity to perform. Eight provincial representative athletes (age = 20 ± 3 years, body mass = 76.2 ± 9.9 kg, height = 179 ± 7cm) volunteered to complete countermovement jump (CMJ) testing twice a week throughout the season, while also monitoring their physical exertion using session rating of perceived exertion (RPE). All data was analysed using R-Studio software. Pearson correlation coefficients, ANCOVA and paired sample t-tests were calculated. The results indicated that relative mean power output significantly increased across the season (p<0.001), with the relationship remaining significant when adjusted to remain within the ACWL ratio of 0.8-1.3. Mean velocity did not appear to have any significant changes throughout the season. However, when adjusted to only include velocity data within 0.8-1.3 ACWL ratio, the relationship became significant indicating a clear relationship (p<0.001). A case study directly investigating the difference between a well-trained and youth athlete revealed that there was a significant difference in mean velocity and relative mean power output (p<0.001). The case study also showed a strong correlation between relative mean power and mean velocity (p<0.001) both inside and outside the identified 0.8-1.3 ACWL zone. A relationship between each individual’s perceived capacity for performance based on quantifiable fatigue was identified. Practitioner’s should look to implement affordable, and efficient monitoring if it helps to inform future strength and conditioning delivery ultimately improving performances.
Keywords: Countermovement jump; Acute chronic workload; Netball; Youth and well trained athletes